(untitled) (Third Sector Social Economic Review, 2026)
In the age of digitalization, leadership is understood not only as encompassing the managerial dimension of technological transformation, but also as a process that brings out the creative and innovative potential of employees. Entrepreneurial intention, which is gaining increasing importance in the literature, is associated with individuals’ desire to implement their own ideas and their level of determination in this direction; it is considered one of the key determinants of innovative attitudes and behaviors. The main objective of this study is to examine the effect of digital leadership on employees’ innovative behaviors and to reveal the mediating role of entrepreneurial intention in this effect. In addition to the direct effect of digital leadership on innovative behavior, the mediating role of entrepreneurial intention in this relationship was analyzed at both theoretical and empirical levels. The findings indicate that, in addition to promoting digital leadership in organizations, supporting entrepreneurial tendencies is also critical for enhancing innovative capacity. The research was conducted on SMEs operating in the province of Kırşehir. Using convenience sampling, a survey was administered to 438 employees and tested using a structural equation model. The findings reveal that digital leadership is a factor that encourages innovative behavior, but this effect becomes more meaningful when reinforced by entrepreneurial intention.